The Introduction of Chemical Therapeutics in Modern Spain - Rey, María (1996)
The treatment used in Spain throughout history undergoes a turning point in the seventeenth century. Surge at this time a controversy between traditionalists and innovators motivated by the delay in the Spanish science was during this period.